Intermodal Transport Systems as A Guiding Factor for Urban Development in The City of Baghdad Within the Framework of Modern Trends (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation systems represent the main part of the components of cities, and the basis for urban planning and design of the city, and each system consists of several parts that work together complementarily within its tracks and in a manner that is integrated with other transportation systems to improve the reality of the city and its positive role in sustainable urban development.Major cities (especially Baghdad) are facing the effects of urban sprawl that supports the spread of private cars, and this has led urban researchers and designers around the world to adopt new urban development trends that included a review of the relationship between transportation systems and urban development in cities.Based on this, the research discusses transportation systems as a guiding factor for urban development according to these trends and studies the possibilities of intermodal transport systems in order to identify the opportunities in Baghdad as one of the major cities that still faces the effects of central planning, design, dispersal, and the expansion of urban tissues directed to cars. The research proposed a possible application strategy, as meeting the requirements of the contemporary city calls for innovative urban design approaches to promote a resilient and livable urban fabric, and transit-oriented development (TOD) is one of these approaches, as this concept increases the use of public transportation, adding value to the area and creates A sense of place and community cohesion, and it provides a dynamic mix of land use that meets the needs of the local population.The research concludes with a set of findings and recommendations that clarify the importance of adopting this strategy to manage more balanced urban growth and develop socially, economically and environmentally sustainable urban societies.